Visual-induced expectations modulate auditory cortical responses - van Wassenhove, Virginie; Grzeczkowski, Lukasz (Frontiers in Neuroscience, 2015)
Active sensing has important consequences on multisensory processing (Schroeder et al. 2010). Here, we asked whether in the absence of saccades, the position of the eyes and the timing of transient colour changes of visual stimuli could selectively affect the excitability of auditory cortex by predicting the “where” and the “when” of a sound, respectively. Human participants were recorded with magnetoencephalography (MEG) while maintaining the position of their eyes on the left, right, or centre of the screen. Participants counted colour changes of the fixation cross while neglecting sounds which could be presented to the left, right or both ears. First, clear alpha power increases were observed in auditory cortices, consistent with participants’ attention directed to visual inputs. Second, colour changes elicited robust modulations of auditory cortex responses (“when” prediction) seen as ramping activity, early alpha phase-locked responses, and enhanced high-gamma band responses in the contralateral side of sound presentation. Third, no modulations of auditory evoked or oscillatory activity were found to be specific to eye position. Altogether, our results suggest that visual transience can automatically elicit a prediction of “when” a sound will occur by changing the excitability of auditory cortices irrespective of the attended modality, eye position or spatial congruency of auditory and visual events. To the contrary, auditory cortical responses were not significantly affected by eye position suggesting that “where” predictions may require active sensing or saccadic reset to modulate auditory cortex responses, notably in the absence of spatial orientation to sounds.